La successione tardo triassica del Gebel di Garian (Libia) : esemplificazione del principio di Walther - Assereto, Riccardo (Rivista italiana di paleontologia e stratigrafia, 1970)
Keywords: Géologie – Djebel Nefousa

L'économique et le social. Expériences tunisiennes - Cornet, Hubert (L'Afrique et l'Asie, 1970)
L'auteur, qui a dirigé pendant quatre ans un groupe de cent tisserands dans l'ile de Djerba, et qui s'est intéressé aussi à une association de maraîchers, réfléchit sur ses expériences. Il constate que les habitudes religieuses de base de l'Islam ont accoutumé les gens à se grouper en corporations, que celles-ci ne fonctionnent pas sur des schémas venus de la capitale, mais grâce à une confiance réciproque, résultant de contacts personnels, et à une claire conscience du bénéfice matériel qu'elles peuvent apporter. Il définit également avec pertinence l'attitude que doit avoir le conseiller technique européen, et le rôle qu'il peut jouer dans les pays en voie de développement (résumé de Maghre-Machrek, 1972/1, n° 49)
Keywords: Artisanat – Djerba

Personnalités tunisiennes: Sadok Ben Jemaa (Mondes arabes, 1970)
Keywords: Biographies – Djerba – 20e siècle

Oman Since 1856: Disruptive Modernization in a Traditional Arab Society - Rentz, George (Journal of the American Oriental Society, 1970)
Keywords: Recension

Les Fouilles de Tegdaoust - Robert, Denise S. (The Journal of African History, 1970)
Keywords: Archéologie – Mauritanie

Misconceptions about the use of monsoons by dhows in East African waters - Datoo, B. A. (East African Geographical Review, 1970)
The East African coast has had maritime contacts with the peripheral lands of the Arabian Sea from time immemorial, and although dhows have been superseded by steamships since the latter part of the nineteenth century, a few still visit East Africa every year. Unless they are equipped with engines, movement of these sailing craft is dependent upon the monsoonal regime of the western Indian Ocean. However, popular ideas about monsoons constitute major misconceptions. These relate to the southern extent of the reliable northeast monsoon employed for the outward journey to East Africa, and the use of the southwest monsoon for the homeward passage to Arabia, Iran and India. This article seeks to correct these misconceptions on the basis of meteorological conditions in the western Indian Ocean, substantiated where possible by empirical evidence, contemporary and historical.
Keywords: Navigation – Zanzibar

Dar es Salaam A sketch of a hundred years - Sutton, J.E.G. (Tanzania Notes and Records, 1970)
Keywords: Zanzibar

Trucial Oman in the 16th and 17th Centuries - Cardi, Beatrice de (Antiquity, 1970)

Cholera in Matrah - Mackirdy, A. (Public Health Reports (1896-1970), 1970)
Keywords: Epidémies – Oman

The Victoria Nyanza as a Trade Route in the Nineteenth Century - Hartwig, Gerald W. (The Journal of African History, 1970)
Keywords: Zanzibar

Djāḥiz et les Khāridjites - Pellat, Charles (Folia Orientalia, 1970)
Keywords: Kharijisme

Review of: Oman since 1856: disruptive modernization in a traditional Arab society by Robert Geran Landen; Oman, a history by Wendell Philips; British interests in the Persian Gulf by Abdul Amir Amin]. - Kelly, J.B. (Middle Eastern Studies, 1970)
Keywords: Recension

Les origines de l’Islam dans les tribus berbères du Sahara occidental: Mūsà ibn Nuṣayr et ʿUbayd Allāh ibn al-Ḥabḥāb - Lewicki, Tadeusz (Studia Islamica, 1970)

L’Adhān presso gl’Ibāḍiti - Rubinacci, Roberto (Folia Orientalia, 1970)
Mainly based on Jannāwunī: Kitāb al-Waḍʿ fī ‘l-Furūʿ. Pp. 285-290: translation of Jannāwunī, 222-237, chapter 3, on the Ādhān. Furthermore based on the commentary on the Kitāb al-Waḍʿ by Abū Sitta al-Qaṣbī (Abū ʿAbdl. Muḥ. b. ʿUmar b. Abī Sitta al-Qaṣbī al-Nafūsī), who used mainly the Kitāb al-Īḍāḥ of Abū Sākin ʿĀmir al-Shammākhī and Jayṭālī’s Qawāʿid and Qanāṭir.
Keywords: Jayṭālī; Ismāʿīl b. Mūsà (13..-1350); Orientalisme – Italie

الخوارج - توفيق, أرشد (مجلة الآداب, 1970)
Keywords: Kharijisme

The Kharijites and the Murjiʼites from Shahrastani's Kitab Al-Milal Waʼl-Niḥal - Kazi, A. K.; Maulvi, Fazil; Flynn, J. G. (Abr-Nahrain, 1970)
Keywords: Kharijisme

Die Mozabiten. Ein anthropologischer Ausflug ins Tal des Mzab - Freund, Wolfgang Slim (Zeitschrift für Kulturaustausch, 1970)
Keywords: Moeurs et coutumes – Mzab

A proposito della terminologia marinaresca zuarina (Immagini comuni ad altre zone del Mediterraneo e prestiti italiani) - Serra, Luigi (Bollettino dell’Atlante Linguistico Mediterraneo, 1970)
Keywords: Linguistique – Zouara

L’ittionimia e la terminologia marinaresca nel dialetto berbero di Zuara (Tripolitania) - Serra, Luigi (Studi Magrebini, 1970)
Keywords: Linguistique – Zouara

Le tourisme à Djerba, répercussions sociales - Freund, Wolfgang Slim (Revue de l'Occident musulman et de la Méditerranée, 1970)
Keywords: Tourisme – Djerba

Croissance urbaine au Sahara : Ghardaïa - Josse, Raymond (Cahiers d'Outre-Mer, 1970)
Archive : Fonds Haouache
Keywords: Urbanisme – Mzab

A description of new Ibadi Manuscripts from North Africa - Nāmī, ʿAmr Khalīfa al- (Journal of Semitic Studies, 1970)
Baḥḥāz 2003a, 194 note 2: Nubdha ʿan Makhṭūṭāt al-Ibāḍiyya bi-Shimāl Ifrīqiyā. A translation by ʿUmar b. Qāsim Mūsà Wāʿalī, with important additions. Printed by Jamʿiyyat ʿAmmī Saʿīd in Ghardaïa, 1998. A translation by Sulṭān b. Mubārak al-Shaybānī, 1970: Waṣf Makhṭūṭāt Ibāḍiyya muktashafa ḥadīthan fī Shimāl Ifrīqiyā. In Sahybānī 2008a, 214-248. For a Turkish translation, see Yıldız, Harun 2015d.
Keywords: Bibliothèques – Djebel Nefousa; Bibliothèques – Djerba; Manuscrits – Djebel Nefousa; Manuscrits – Djerba